Analisis Penerapan Aplikasi Sistem Informasi Kearsipan Dinamis Terintegrasi (SRIKANDI) pada Instansi X - Tessalonika Sitinjak; Henry Eryanto; Suherdi Suherdi (Lembaga Pengembangan Kinerja Dosen, 2025)
Developments in technology and information systems provide changes and play an important role in people's lives. In government, these developments can increase the effectiveness and efficiency of the government system. The government made innovations in archiving by launching the Integrated Dynamic Archives Information System (SRIKANDI) application to create convenience in organizing correspondence and archiving processes. The purpose of this research is to find out how the implementation of the SRIKANDI application at agency X. This research is qualitative research with data collection techniques through observation, interviews, and documentation. Sampling in this study used a non-probability sampling method with a purposive sampling method. The results showed that the application of the SRIKANDI application at agency X provides many benefits and conveniences in managing letters and archives. However, there are still shortcomings in its application, namely the quantity of use in each work unit that is still different, leadership commitment, and conventional processes that are still carried out simultaneously. The obstacles in the process of implementing this application are applications or servers that are often slow or down, not all employees are skilled in using the application, and application security that cannot be 100% guaranteed from data leaks or hackers.